2013
DOI: 10.3892/mmr.2013.1602
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of tyrosinase is a determinant of melanin production in cultured melanoma cells

Abstract: Abstract. The majority of malignant melanoma cell types are able to produce melanin and the degree of melanin synthesis in various types of cultured cell line differs. In this study, we evaluated three types of cultured cell line, MNT-1, HM3KO and G-361, with differing melanin production levels. The level was greatest in the MNT-1 cells, lower in the HM3KO cells and lowest in the G-361 cells. In addition, a positive correlation between melanin production and tyrosinase activity was observed. The molecular mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…As tyrosinase is a metalloenzyme with two copper ions; chelators that can sequester copper have also shown promise as a target for pigmentation disorders [ 14 , 15 , 16 ]. The intracellular transport of tyrosinase is regulated by copper uptake and the N-glycosylation process [ 17 ]; the role of the enzyme α-glucosidase has been implicated in this glycosylation process in previous reports [ 18 , 19 ]. Consequently, certain antidiabetic drugs such as voglibose [ 20 ] and acarbose [ 21 ], which are known to inhibit α-glucosidase activity, also suppress melanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…As tyrosinase is a metalloenzyme with two copper ions; chelators that can sequester copper have also shown promise as a target for pigmentation disorders [ 14 , 15 , 16 ]. The intracellular transport of tyrosinase is regulated by copper uptake and the N-glycosylation process [ 17 ]; the role of the enzyme α-glucosidase has been implicated in this glycosylation process in previous reports [ 18 , 19 ]. Consequently, certain antidiabetic drugs such as voglibose [ 20 ] and acarbose [ 21 ], which are known to inhibit α-glucosidase activity, also suppress melanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the cell, N-glycosylation plays an essential role in the transfer of tyrosinase from ER to the cytoplasm and in maintaining its folding, stability, and enzymatic activity (Imokawa and Mishima, 1984; Branza-Nichita et al, 2000; Wang and Hebert, 2006). The glycosylation of tyrosinase might regulate the melanin production in different types of cultured melanoma cells (Mikami et al, 2013). It has been proven in mouse melanoma cells, that inhibition of the early steps of the N-glycosylation process strongly affects tyrosinase activity, thereby changing melanin synthesis.…”
mentioning
confidence: 99%
“…In this study, recombinant wild-type and mutant human tyrosinase enzymes were overexpressed in E. coli BL21 (DE3) and utilised to analyse the catalytic activity. It has been reported that N-glycosylation is necessary for human tyrosinase stability and activity in vivo [29][30][31] . However, our previous studies and those of another group have also shown that recombinant human tyrosinase from E. coli could exhibit activity without phosphorylation or glycosylation 18,24,32 .…”
Section: Discussionmentioning
confidence: 99%